International aid is a means to cover up the illegitimacy of governments. - Ahmed Khalf Hussein AL-Dakhil; M.A. Wendy Burgess (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
This study deals with the use of governments of rich countries that are unpopular and do not use democratic means of access to power. International subsidies are used to bribe influential countries in the international community, both at the global and regional levels, through international aid under pretexts and justifications Including titles such as cooperation in the fight against terrorism, the strengthening of relations between the two countries, the response to humanitarian disasters, the consolidation of democracy and the protection of human rights, among others. This leads the beneficiary countries to silence the illegal practices of Governments in access to power and violations of human rights, as well as recent models of these practices (payment of international subsidies) by countries that support the political change of illegal rule in another country by overpaying international subsidies to these illegal governments to overcome the financial difficulties faced by To improve its image in front of the masses to appear as a savior of the latter from the financial problems intractable to see that political change in governance as a revolution and not a coup, thus contributing to the legitimacy of that provision.